A new variable structure DC motor controller using geneticalgorithms - Al-Hamouz, Z.M. (1998)
This paper presents a new application of the genetic algorithm for the selection of the variable structure controller (VSC) feedback gains and switching vector for a separately excited DC motor. Contrary to the VSC design methods reported in the literature, the method provides an optimal and systematic design procedure for the selection of the feedback gains and switching vector. By the proposed VSC controller, the speed of a tested DC motor follows a pre-determined speed track to a high degree of accuracy. The proposed controller has been found to be robust against high variations in the motor parameters